Pengaruh Faktor Sosial Ekonomi terhadap Mobilitas Tenaga Kerja Antarsektor dan Antarwilayah pada Rumah Tangga Petani di Pedesaan Kabupaten Jember - Sebastiana, . (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2003)
Social economics factor have a strong relationship with people motivation to under take among sector and among regions migration in the villages. The Study aimed to know the effect of income, farm land ownership, formal education, non formal education, job opportunities in non agricultural sector, age, gender, marital status, and number family members on the decision of formers household family members to under lake among sector and among-regions mobility. The linier Probability Model (LPM), statistics tests (coeficient of determination, partial t test, simultan F test) and classical assumption were used to examine the effect of social economy factor on labour mobility decision. Based o n the resuh and discussion,i t is concluded that : (1) income and width of farmers owned land significantly influenced (2) a relatively low farmers household income in agriculture sector in almost all villages had significantly contributed to the interest of farmers and farm labourers to migrated from agriculture sector; and (3) age factor was also a variable that significantly influence the among-sector labour mobility.